Total Lemak Tubuh Hasil Pengukuran Bioelectrical Impedance Analysis Berhubungan dengan Status Gizi pada Remaja Awal di Kota Yogyakarta, Indonesia: Association between Total Body Fat Measured by Bioelectrical Impedance Analysis and Nutritional Status among Early Adolescents in Yogyakarta City, Indonesia - Syagata, Anindhita Syahbi; Shafriani, Nazula Rahma; Khairani, Khalisa; Martuti, Sri; Widyantara, Aji Bagus; Muslikah, Erina Dwi; Raharjo, Fitri Ayu (Amerta Nutrition, 2025)
Background: Stunting and obesity remain major nutritional challenges among Indonesian children and adolescents, including Yogyakarta. While stunting reflects chronic undernutrition, prevalence of obesity during adolescence is increasing and is associated with metabolic disorders. The relationship between lipid profiles, total body fat, and nutritional status during adolescence require further investigation. Objectives: To analyze the relationships between total cholesterol levels, total body fat, and nutritional status based on BMI-for-age z-score (BAZ) and height-for-age z-score (HAZ) among early adolescents in Yogyakarta City. Methods: This cross-sectional study involved 116 elementary school students from Muhammadiyah elementary schools in Yogyakarta City selected through cluster-random sampling. Anthropometric measurements were obtained using a microtoise and Body Impedance Analysis (BIA), while biochemical parameters were assessed using Glucose, Cholesterol, and Uric Acid (GCU) meter. Data were analyzed using Pearson and Spearman correlation tests based on data normality. Results: There was no significant relationship between total cholesterol and nutritional status (BAZ or HAZ) in either sex. However, total body fat was significantly associated with BAZ in both males and females (r=0.67 and r=0.79, respectively; p-value<0.05). A significant association was also observed between total body fat and HAZ in males (r=-0.29, p-value=0.026). Additionally, BAZ and HAZ were significantly correlated (r=0.19, p-value=0.039), suggesting a link between stunting and obesity indicators. Conclusions: Total body fat is strongly associated with overweight and obesity (BAZ) in both males and females; and weakly associated with stunting (HAZ) in boys. Total cholesterol, however, is not a sensitive marker of nutritional status in this population.